2003
DOI: 10.1074/jbc.m308295200
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage-induced MDMX Degradation Is Mediated by MDM2

Abstract: Although genetic studies have demonstrated that MDMX is essential to maintain p53 activity at low levels in non-stressed cells, it is unknown whether MDMX regulates p53 activation by DNA damage. We show here that DNA damage-induced p53 induction is associated with rapid down-regulation of the MDMX protein. Significantly, interference with MDMX down-regulation results in the suppression of p53 activation by genotoxic stress. We also demonstrate that DNA damage-induced MDMX reduction is mediated by MDM2, which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
152
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(173 citation statements)
references
References 14 publications
20
152
1
Order By: Relevance
“…As well as promoting ubiquitination of p53, Mdm2 promotes the ubiquitination and proteasomal degradation of MdmX (Kawai et al, 2003). In this study, we observed that ectopically expressed USP2a deubiquitinates MdmX and consequently inhibits Mdm2-mediated MdmX degradation.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…As well as promoting ubiquitination of p53, Mdm2 promotes the ubiquitination and proteasomal degradation of MdmX (Kawai et al, 2003). In this study, we observed that ectopically expressed USP2a deubiquitinates MdmX and consequently inhibits Mdm2-mediated MdmX degradation.…”
Section: Discussionmentioning
confidence: 58%
“…It has been shown that some p53-activating stresses result in a decrease in the stability of MdmX and consequently a decrease in MdmX protein levels (Kawai et al, 2003;Gilkes et al, 2006). To investigate whether changes in USP2a expression could be involved in regulation of MdmX following stress NTERA-2 cells were treated with 20 mM cisplatin for between 2 and 10 h as indicated (Figure 5a).…”
Section: Usp2a Is Downregulated By Cisplatinmentioning
confidence: 99%
See 2 more Smart Citations
“…MDM2's inherent instability stems from its capacity to self-ubiquitylate (Kawai et al, 2003). As G3BP2 overexpression suppressed MDM2-mediated p53 ubiquitylation, we wanted to know if G3BP2 could also interfere with MDM2 auto-ubiquitylation.…”
Section: Resultsmentioning
confidence: 99%